Lutzomyia longipalpis (Diptera, Psychodidae, Phlebotominae) and urbanization of visceral leishmaniasis in Brazil Lutzomyia longipalpis (Diptera, Psychodidae, Phlebotominae) e urbanização da leishmaniose visceral no Brasil - Elizabeth F. Rangel; Maurício L. Vilela (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2008)
The article discusses habits related to the vectorial competence of Lutzomyia longipalpis, along with evidence confirming the importance of this sand fly species in the epidemiological chain of visceral leishmaniasis in Brazil. A new epidemiological profile for visceral leishmaniasis is also postulated, associated with domestic environments and the role of Lu. longipalpis in this process, its sylvatic origin, and its capacity to adapt to a wide range of habitats. Another sand fly species, Lu. cruzi, is mentioned as a vector of visceral leishmaniasis in some municipalities in Central Brazil, based on studies in endemic areas of the country. São apresentados os hábitos que condicionam a competência vetorial de Lutzomyia longipalpis e discutidas as evidências que confirmam a importância deste flebotomíneo na cadeia de transmissão da leishmaniose visceral no Brasil. Discute-se, também, o novo perfil epidemiológico da leishmaniose visceral, associado à ambientes urbanos, e o papel desempenhado por Lu. longipalpis neste processo, sua origem silvestre e capacidade de adaptação. É citado outro flebotomíneo, Lu. cruzi, como transmissor em alguns municípios da região central do Brasil, com base em estudos realizados em áreas endêmicas.